2015
DOI: 10.1016/j.plabm.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analytical performance of the novel NS-Prime system and examination of temperature stability of fecal transferrin compared with fecal hemoglobin as biomarkers in a colon cancer screening program

Abstract: ObjectiveTo examine the analytical aspects of fecal transferrin (Tf) and hemoglobin (Hb) measured on the NS-Prime analyzer for use in a colon cancer screening program.Designs and methodsMethod evaluation and temperature stability studies for fecal Tf and Hb were completed. A method comparison was carried out against the NS-Plus system using samples collected from 254 screening program participants. A further 200 samples were analyzed to help determine suitable reference limits for fecal Tf using these systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…3 Most publications on f-Hb sample stability have focused on the stability of f-Hb after sample collection into specialized collection devices. [11][12][13] Previous work on stability of f-Hb in faeces using FIT methodology utilized normal faeces spiked with haemoglobin and showed rapid instability at room temperature. 10 Most diagnostic accuracy studies using FIT have provided patients with a specialized collection device for sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most publications on f-Hb sample stability have focused on the stability of f-Hb after sample collection into specialized collection devices. [11][12][13] Previous work on stability of f-Hb in faeces using FIT methodology utilized normal faeces spiked with haemoglobin and showed rapid instability at room temperature. 10 Most diagnostic accuracy studies using FIT have provided patients with a specialized collection device for sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 15 studies were identified by our search strategy of literature that studied biomarkers in FIT buffer from FIT samples that had been created by lab personnel (rather than patients) from patient whole stool samples. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] These studies were not included in this systematic scoping review since the technique to obtain the sample (capturing a whole stool) and the placement into the device (spiking by lab personnel) could impact both the stability of the biomarkers detected and the test characteristics for the biomarkers examined. For example, transporting whole stool to the lab may be associated with more degradation in transit or the lab personnel may spike greater stool into the FIT collection device than might be accomplished in actual clinical practice from a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 15 studies were identified by our search strategy of literature that studied biomarkers in FIT buffer from FIT samples that had been created by lab personnel (rather than patients) from patient whole stool samples 41–55 . These studies were not included in this systematic scoping review since the technique to obtain the sample (capturing a whole stool) and the placement into the device (spiking by lab personnel) could impact both the stability of the biomarkers detected and the test characteristics for the biomarkers examined.…”
Section: Discussionmentioning
confidence: 99%